Speaking Acquaintances or Helpers in Need: Participation in Civic Associations and Individual Social Capital - Michael Mutz; Ulrike Burrmann; Sebastian Braun (VOLUNTAS: International Journal of Voluntary and Nonprofit Organizations, 2020)
It is widely believed that civic associations are capable to produce social capital, here understood as an individual asset resulting from relations of mutual support and assistance. Although hardly anybody denies that socializing is widespread in many civic associations, it still remains to be shown that this socializing provides a genuine commitment to support. This paper explores the relationship between involvement in civic organizations and social support. The data analysed come from a nation-wide survey “Organized Sport and Social Capital—Revisited” (OSSCAR) representing the adult population in Germany. Findings show that participation in civic associations is associated with higher levels of social support. This effect is stronger for active participants and weaker for passive members. Path analyses further indicate that this effect is mediated by a person's sociability orientations as well as her commitment to prosocial values. These findings help providing a more nuanced understanding of mechanisms of social capital formation in civic associations.
Keywords: 300; Social capital; Social connectedness; Social support; Civic associations; Civil society